Automotive engineering fundamentals - Stone, Richard (Society of Automotive Engineers, 2004)
From engines and transmissions to vehicle aerodynamics and computer modeling, the intelligent, interesting presentation of core concepts in Automotive Engineering Fundamentals is sure to make this an indispensable resource for engineering students and professionals alike.
Title from PDF title page (SAE Web site, 08/03/2012).
Keywords: Automobiles -- Design and construction.; elektronické knihy; electronic books